Kajian Yuridis Pengesahan Perkawinan di Pengadilan Agama Jember (Studi Kasus Putusan Pengadilan Agama Jember Tentang Pengesahan Perkawinan di Bawah Tangan) - Imam Bukhori (FALASIFA : Jurnal Studi Keislaman, 2016)
Marriage can be said to be valid if done according to Islamic law and in accordance Law - Marriage Law and the Compilation of Islamic Law. Indonesian legal system does not recognize the term under the hand mating, marriage Sirri and the like, and do not set out specifically in a regulation. For those who do not register marriages considered invalid in the eyes of the law and did not get a marriage certificate as proof of the validity of a marriage is authentic. But in the Compilation of Islamic Law article 7 paragraph (2) states: "in the case of marriage can not be proven with a marriage certificate can be submitted ithbat nikahnya Religious Court". Moderate paragraph (3) states ithbat marriage that can be submitted to the Court with respect to religion; a. Their marriage in a divorce settlement, b. The loss of a marriage certificate, c. The existence of doubt on the legitimacy of one of the conditions of marriage, and d. Marriage occurred prior to the enactment of Act 1 of 1974 on marriage, e. Marriages performed by those who have no impediment of marriage according to Law No. 1 of 1974. To address this problem researchers use empirical normative approach. As is the normative approach is an effort to bring the issues examined by the normative law. While the empirical approach is an attempt to approach the issues examined by real law or in accordance with the reality that exists in the community. The source of the data in this research is purposive sampling and techniques used in data collection are: 1.Observasi, 2. Interview 3. Documentation. Related to this research, analysis of the data used is descriptive analysis. Namely the operation of the data by describing the social reality / empirical (in this case the products of court decision), with the existing theory (laws that are relevant to the case) The results of the study show that the first: Jember Religious Court granted the petition would remain despite the legalization of marriage marriage under the hand, all the marriage was held meet Islamic law and the marriage does not violate the prohibition on marriage datur in Article 8 to Article 10 of Law No. 1 of 1974 in conjunction with Article 39 through Article 44 Compilation of Islamic Law. Second: The judges Religious Court Jember will still grant Type Approval of Marriage in the Lower Hand / ithbat marriage if the marriage of the applicant that has been done previously qualified and harmonious marriage despite his marriage under the hand / marriage Sirri, that into consideration Court judge Religion Jember is benefit for the Petitioner and the child's future ratification applicant wedding / marriage istbat.Key Word: Overview juridical Marriage Endorsement.